Use of photodynamic inactivation for in vitro reduction of prevalent bacteria in Fournier's Gangrene - Pereira,Nalisson Marques (2018)
ABSTRACT Fournier's Gangrene (FG) is an infectious disease caused by several synergic microbes, with high morbidity and mortality rates; therefore, the search for new less invasive and mutilating treatments, with faster recovery, has been proposed. Surgical intervention, the use of several systemic and topic antibiotics, and hyperbaric oxygen therapy are currently the best approach for the treatment of these patients. The use of Photodynamic Inactivation (PDI) aims to lower morbidity and mortality, by reducing bacterial microbiota and speeding wound healing. In the present study, viable bacteria were separated in four groups: Group L-/F- (no irradiation with red laser and absence of methylene blue photosensitizer), Group L-/F+ (no irradiation with red laser and presence of methylene blue), Group L+/F- (irradiation with red laser and absence of methylene blue) and L+/F+ (irradiation with red laser associated to methylene blue). In all groups, exposure time to treatment was 5, 10 and 15 minutes. The concentration of methylene blue photosensitizer was 0.1mg/L, and the dose of red laser (660nm wave length) was 176.9mW/cm2. Following irradiation, the reduction of number of bacteria was evaluated, and the results were expressed in colony forming units (CFU) and as exponential reduction. As the main results, in the L+/F+ group, there were no Clostridium perfringens and Staphylococcus aureus CFUs and there was a reduction of Escherichia coli that was not observed in the other groups.